2014
DOI: 10.1186/1472-684x-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences and priorities for end-of-life care in Kenya: a population-based street survey

Abstract: BackgroundEnd-of-life care needs are great in Africa due to the burden of disease. This study aimed to explore public preferences and priorities for end-of-life care in Nairobi, Kenya.MethodsPopulation-based street survey of Kenyans aged ≥18; researchers approached every 10th person, alternating men and women. Structured interviews investigated quality vs. quantity of life, care priorities, preferences for information, decision-making, place of death (most and least favourite) and focus of care in a hypothetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 39 publications
6
50
0
5
Order By: Relevance
“…The decisions on end of life care are preferably deferred to family members or community elders [9]. In Kenya, for example, 68.2% of respondents in one study indicated they would like a relative to be involved in end of life decision making [10]. The study was a population-based survey of public preferences and priorities for end of life care in Kenya done in Nairobi and Western Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…The decisions on end of life care are preferably deferred to family members or community elders [9]. In Kenya, for example, 68.2% of respondents in one study indicated they would like a relative to be involved in end of life decision making [10]. The study was a population-based survey of public preferences and priorities for end of life care in Kenya done in Nairobi and Western Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Third, an important variable in analysis of place of death might be the availability of palliative care services. In Africa, preference for dying at home4 5 was found to be lower than that in Europe,6 using similar study methods. In low and middle income settings where palliative care coverage is poor, and few health resources are available in the home, a home death could potentially be a very poor death indeed.…”
mentioning
confidence: 65%
“…[8][9][10][11][12] Surveys have suggested that Kenyans want to know if their lives will end soon and want their families to be involved in the discussion. 13 Patients of many cultures consider spirituality to be important by the end of their lives, 4,5,14-16 and palliative-care patients who consider themselves to be more spiritually-oriented also tend to report less spiritual pain, depression, and anxiety. 17,18 Therefore, we should overcome our perceived awkwardness in approaching the subject of death and provide the spiritual balm our patients need.…”
Section: Question 4: Do We Respect the Cultural Taboo Which Shuns Spementioning
confidence: 99%